Mexico : what kind of transition? - FIDLER, Stephen (1996)
Examines the prospects for a genuine transition to democracy in Mexico under the administration of President Zedillo and his successors. Concludes that it is unlikely that the transition to democracy can be accomplished quickly or without further violence.